Not in vain ; 19th what God hath wrought amongst the Kanakas being Report of the Solomon Island Branch and Nineteenth annual report of the Queensland Kanaka Mission for the year 1904-1905 (1905)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Queensland Kanaka Mission Solomon Island Branch; Brethren movement -- missions -- Australia -- history